Preparing Successors for Leadership Another Kind of Hero - Aronoff, C.; Ward, J.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2011)
The founders of the family business must impart their vision and leadership to succeeding generations. Preparing those generations for leadership is challenging and encompasses a lifetime. Aronoff and Ward's strategy for a smooth transition prepares successors for their role in the future of the firm.
Keywords: Management; Organization; Planning; Small business; Leadership; Entrepreneurship; Family-owned business enterprises; Management; Organization; Small Business; Business Strategy/Leadership.; Entrepreneurship; Family Business